Vloga prve skrbstvene sestre Angele Boškin pri profesionalizaciji slovenske zdravstvene nege - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2019)
Introduction: Understanding the history of nursing enhances the capacity and positive self-image of nursing professionals, and helps them develop critical thinking and decision-making skills. The aim of the research was to investigate the professional work of Ms. Angela Boškin through the theoretical framework of professionalization elements in nursing.Methods: Historical research design with idealistic tradition and biographical approach were used. A total of 16 sources of different typologies were included in content analysis and synthesis of evidence. The methods of paraphrasing, chronological classification system, content categorization, and content themes were used. Reliability and validity of the research were evaluated using external and personal information evaluation, balance of content, and familiarization with the historical period.Results: A total of 122 paraphrases were produced and subsequently merged into 31 categories and 10 themes describing Ms. Angela Boškin's contribution to the professionalization of Slovenian nursing care in the period 1912%1944. The themes served as the basis for composing the story and drawing conclusions. Discussion and conclusion: Ms. Angela Boškin provided the initial expertise needed to establish nursing as an occupation in Slovenia and contributed to the development of its autonomy, professional recognition and social esteem. By founding the first school, Ms. Boškin laid the foundations for the development of basic professional knowledge and standardized education. She established the autonomy of preventive care to mothers and children, and contributed to the adoption of a regulatory framework for 'social care nurse' in preventive nursing care. As the head of the nursing association, she set the direction for the development of nursing care, giving it value in Slovenia and internationally.
Keywords: association; Boškin, Angela; društvo; history; izobraževanje; medicinske sestre; nurses; occupation; profesija; profession; skrb; stroka; zgodovina